2022
DOI: 10.3389/fgene.2022.832542
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Anthesis Drought Stress on Physiology, Yield-Related Traits, and Drought-Responsive Genes in Green Super Rice

Abstract: Optimum soil water availability is vital for maximum yield production in rice which is challenged by increasing spells of drought. The reproductive stage drought is among the main limiting factors leading to the drastic reduction in grain yield. The objective of this study was to investigate the molecular and morphophysiological responses of pre-anthesis stage drought stress in green super rice. The study assessed the performance of 26 rice lines under irrigated and drought conditions. Irrigated treatment was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Crops are frequently faced with different biotic and abiotic stresses that limit their development, causing impressive decreases in farming production all over the world [ 25 , 39 , 40 ]. Plants are immobile and take essential nutrients, and water from the soil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Crops are frequently faced with different biotic and abiotic stresses that limit their development, causing impressive decreases in farming production all over the world [ 25 , 39 , 40 ]. Plants are immobile and take essential nutrients, and water from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…SSI was also used previously to calculate the stress susceptible index [ 69 , 70 ]. Previously it is reported that S3 is a drought-sensitive genotype [ 25 ]. In this study, we also found that S3 and S24 are salt-susceptible genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought stress during grain filling stage increases the proportion of chalky grains ( Yang et al., 2018 ). The imposition of drought stress at the onset of anthesis for 30 days reduced the grain yield and harvest index of 25 rice genotypes, with reduced pollen fertility and test weight of grains for most genotypes, compared to irrigated conditions ( Ahmad et al., 2022 ). While leaf rolling is considered a defense mechanism against drought stress, its promptness correlated with anatomical traits rather than water deficit ( Nithya et al., 2021 .…”
Section: Physiological and Molecular Implications Of Individual Stres...mentioning
confidence: 99%